Post-injury immunosuppression and secondary infections are caused by an AIM2 inflammasome-driven signaling cascade - Roth, Stefan; Cao, Jiayu; Singh, Vikramjeet; Tiedt, Steffen; Hundeshagen, Gabriel; Li, Ting; Boehme, Julia D.; Chauhan, Dhruv; Zhu, Jie; Ricci, Alessio; Gorka, Oliver; Asare, Yaw; et al. (Immunity, 2021)
Loss of lymphocytes, particularly T cell apoptosis, is a central pathological event after severe tissue injury that is associated with increased susceptibility for life-threatening infections. The precise immunological mechanisms leading to T cell death after acute injury are largely unknown. Here, we identified a monocyte-T cell interaction driving bystander cell death of T cells in ischemic stroke and burn injury. Specifically, we found that stroke induced a FasL-expressing monocyte population, which led to extrinsic T cell apoptosis. This phenomenon was driven by AIM2 inflammasome-dependent interleukin-1β (IL-1β) secretion after sensing cell-free DNA. Pharmacological inhibition of this pathway improved T cell survival and reduced post-stroke bacterial infections. As such, this study describes inflammasome-dependent monocyte activation as a previously unstudied cause of T cell death after injury and challenges the current paradigms of post-injury lymphopenia.